Historical background of wood-fired ceramics firing in cross-flow kilns - Volodymyr Khyzhynskyi; Olena Оsadcha; Leonid Nagirniak (Історія науки і техніки, 2025)
This work is a comprehensive study that covers the historical, technical and creative aspects of the unique process of wood firing of ceramics. The conducted research allowed to understand the essence of wood firing, its aesthetic and cultural value more deeply. Analysis of the historical development of wood firing revealed its deep roots in the cultural traditions of different peoples. This technique, which originated thousands of years ago, remains relevant due to its ability to create unique textures, effects and emphasize the natural beauty of the material. The historical aspect shows how wood firing has transformed from a utilitarian process into an important artistic tool. A key feature of wood firing is the use of special kilns designed to maintain high temperatures for a long time. Research into different types of cross-flow wood kilns revealed their technical features and impact on the final result. It has been established that the firing process depends on many factors, including the type of wood, the atmosphere of the kiln, the temperature and the duration of firing. These parameters form the unique character of each product. The use of wood firing for artistic purposes allows to achieve unique visual effects, such as natural ash pouring, textured surfaces, natural color transitions. Wood firing is a unique process that combines tradition and innovation, technology and art. Its significance lies in the ability to create objects that are not only visually striking, but also carry a deep emotional content. This technique requires skill, patience and understanding of the material, as well as the willingness to work with the element of fire, which becomes a full-fledged co-author. The research conducted not only deepened knowledge about wood firing, but also showed its limitless possibilities for creative expression. The study demonstrates that this technique remains relevant and inspiring for contemporary artists, offering endless opportunities for discovery in the field of artistic ceramics. The technology of wood firing in cross-flow kilns continues to develop, and its capabilities open up new horizons for contemporary ceramic art. Wood firing is not only a technology, but also a philosophy. It reflects the interaction of man with nature and fire, allowing the creation of unique ceramic products that cannot be repeated. This is precisely its value and unfading relevance in the world of ceramic art.